INFORMATION SYSTEM ON THE ACCEPTANCE OF GOODS COUNTER BOOK SHOP GIANT BRANCH KARISMA SERPONG USING MICROSOFT VISUAL BASIC 6.0 - Catharina Evi Indriyati; Irfan, SKom, MMSI Irfan, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Karisma bookstore Serpong Giant Branch is a branch of the PT. Karisma Mediatamascript now engaged in the retail sale of products includes all kinds of books,magazines, school supplies and office appliances.In the procurement of products Bookstores Serpong supply Karisma Giant Branch ofthe Central Office, while for the procurement of supplies magazine products directlyfrom suppliers with the approval of headquarters and provided counter placement.Until now the administration system for receiving goods counter at Giant BranchBookstores Karisma Serpong still are semi computer, only using Microsoftapplications Micrsoft Word and Excel. By using this application processing and dataentry is too complicated so that the data double frequent, complex searches of dataand preparing reports semi-automatic.In order to overcome the existing problems we need a good information system,practical and computerization are expected to improve efficiency and effectiveness inthe process of collecting data and preparing reports, the authors propose solving theproblem by creating an information system in order to solve these problems.